2019
DOI: 10.1093/jme/tjz086
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Flying Insects in Seven Hospitals in the United Kingdom and Carriage of Bacteria by True Flies (Diptera: Calliphoridae, Dolichopodidae, Fanniidae, Muscidae, Phoridae, Psychodidae, Sphaeroceridae)

Abstract: Insects are efficient vectors of bacteria and in the hospital environment may have a role in spreading nosocomial infections. This study sampled the flying insect populations of seven hospitals in the United Kingdom and characterized the associated culturome of Diptera, including the antibiotic resistance profile of bacterial isolates. Flying insects were collected in seven U.K. hospitals between the period March 2010 to August 2011. The bacteria carried by Diptera were isolated using culture-based techniques,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 43 publications
1
11
0
1
Order By: Relevance
“…As previously discussed, flies play a key role in the transmission of diseases and decomposition procedure of human corpse [1,9]. In this study, we used maggots to study diversity and succession patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously discussed, flies play a key role in the transmission of diseases and decomposition procedure of human corpse [1,9]. In this study, we used maggots to study diversity and succession patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Diptera is one of the most important insects within the public health and forensic fields, due to their involvement in the transmission of diseases and also estimation of post mortem interval (PMI), PMI is the period of time between insects' establishment of corpses and their finding by the examiner [1,2]. Dipteran species are efficient vectors of over 100 pathogens, including bacteria, viruses, fungi, and parasites and they could have an important role in dissemination nosocomial infections [1,3]. In the term of forensics, flies may be used to determine the location of death, detection of the abuse of disabled people, identification of the deceased, and estimation of post mortem interval [4 -6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of antibiotic-resistant E. coli from flies captured in a livestock facility was thus unsurprising [3]. Another study has shown that houseflies from hospitals in the UK carried different bacteria resistant to antibiotics [4]. We investigated if houseflies captured in a tertiary hospital in Rwanda carried clinically relevant MRGN pathogens.…”
mentioning
confidence: 99%
“…Our results demonstrate that half of the flies in this tertiary hospital in Rwanda carried virulent MRGN pathogens including the pathogenic clonal E. coli lineage ST131. High pre-admission and even higher discharge rates at this facility [5] may suggest that a) patients and caregivers were the source of MRGN for the flies and b) that flies play a role in the transmission of antimicrobialresistant pathogens within clinics and in mirroring the burden of antimicrobial resistance [4] at that time. Even though the actual transmission of MRGN bacteria through flies to humans awaits verification, respective modelling results point strongly into this direction [11].…”
mentioning
confidence: 99%